1200 years of decadal-scale variability of Mediterranean vegetation and climate at Pantelleria Island, Italy - Calò, Camilla; Henne, Paul D.; Eugster, Patricia; van Leeuwen, Jacqueline; Gilli, Adrian; Hamann, Yvonne; La Mantia, Tommaso; Pasta, Salvatore; Vescovi, Elisa; Tinner, Willy (HOLOCENE, 2013)
A new sedimentary sequence from Lago di Venere on Pantelleria Island, located in the Strait of Sicily between Tunisia and Sicily was recovered. The lake is located in the coastal infra-Mediterranean vegetation belt at 2 m a.s.l. Pollen, charcoal and sedimentological analyses are used to explore linkages among vegetation, fire and climate at a decadal scale over the past 1200 years. A dry period from ad 800 to 1000 that corresponds to the Medieval Warm Period' (WMP) is inferred from sedimentological analysis. The high content of carbonate recorded in this period suggests a dry phase, when the ratio of evaporation/precipitation was high. During this period the island was dominated by thermophilous and drought-tolerant taxa, such as Quercus ilex, Olea, Pistacia and Juniperus. A marked shift in the sediment properties is recorded at ad 1000, when carbonate content became very low suggesting wetter conditions until ad 1850-1900. Broadly, this period coincides with the Little Ice Age' (LIA), which was characterized by wetter and colder conditions in Europe. During this time rather mesic conifers (i.e. Pinus pinaster), shrubs and herbs (e.g. Erica arborea and Selaginella denticulata) expanded, whereas more drought-adapted species (e.g. Q. ilex) declined. Charcoal data suggest enhanced fire activity during the LIA probably as a consequence of anthropogenic burning and/or more flammable fuel (e.g. resinous Pinus biomass). The last century was characterized by a shift to high carbonate content, indicating a change towards drier conditions, and re-expansion of Q. ilex and Olea. The post-LIA warming is in agreement with historical documents and meteorological time series. Vegetation dynamics were co-determined by agricultural activities on the island. Anthropogenic indicators (e.g. Cerealia-type, Sporormiella) reveal the importance of crops and grazing on the island. Our pollen data suggest that extensive logging caused the local extinction of deciduous Quercus pubescens around ad1750.
The following values have no corresponding Zotero field: pub-location: 1 OLIVERS YARD, 55 CITY ROAD, LONDON EC1Y 1SP, ENGLAND publisher: SAGE PUBLICATIONS LTD
Keywords: '"Little Ice Age' (LIA); 'Medieval Warm Period' (MWP); central Mediterranean; Fire history; Pinus pinaster; Quercus ilex; Quercus pubescens; vegetation history

Forest microhabitats differentially influence seedling phenology of two co-existing Mediterranean oak species - Monnier, Yogan; Prévosto, Bernard; Ripert, Christian; Corbani, Aude C.; Fernandez, Catherine (Journal of Vegetation Science, 2012)
Question How do forest microhabitats impact seasonal microclimate conditions and phenological seedling strategies in two co-occurring Mediterranean Quercus species with different leaf habits? Location Pinus halepensis woodlands, Provence, SE France. Methods Ninety sets of three acorns of Quercus ilex (evergreen) or Quercus pubescens (winter-deciduous) were sown under various P. halepensis canopy cover conditions. Canopy cover and litter depth were measured at each sowing point, and soil moisture and temperature were measured twice monthly. Seedling phenology and aerial development were monitored during the second growing season under different microhabitats. Results During rainy periods, soil moisture was higher under open canopy and thinner litter layers, whereas during summer drought soil moisture was higher under dense canopy and thicker litter layers. Quercus pubescens seedlings had higher growth activity than Q. ilex before summer drought, whereas the pattern reversed during autumnal growth. Dense canopy cover strongly delayed budburst and decreased foliar development in Q. pubescens, which was more affected than Q. ilex. Depending on species phenology, litter thickness can influence height growth of flushes during early summer. Conclusions Quercus pubescens has a phenological strategy to allow development of maximal foliar area before summer drought, a typical growth strategy of Mediterranean winter-deciduous species. In contrast, later phenological activity of evergreen Q. ilex enables it to cope with the dry period and capitalize on autumnal precipitation events. Dense cover acts as shelter in the dry season but can reduce soil moisture during wetter seasons. In contrast to Q. ilex, Q. pubescens appeared strongly dependent on canopy cover, suggesting that Q. ilex has a larger regeneration niche in Aleppo pine woodlands. In the context of global change, this ‘microhabitat effect’ on species-specific phenological strategy underlines the need to consider effects of local environmental conditions on regenerating species.
Keywords: Canopy; litter; Phenology; Quercus ilex; Quercus pubescens; Soil moisture; Survival

Variation in cold hardiness and carbohydrate concentration from dormancy induction to bud burst among provenances of three European oak species - Morin, Xavier; Améglio, Thierry; Ahas, Rein; Kurz-Besson, Cathy; Lanta, Vojtěch; Lebourgeois, François; Miglietta, Franco; Chuine, Isabelle (Tree Physiology, 2007)
Although cold hardiness is known to be a major determinant of tree species distribution, its dynamics and the factors that regulate it remain poorly understood. Variation in cold hardiness and carbohydrate concentration, from dormancy induction until bud burst, were investigated in populations of two deciduous (Quercus robur L. and Quercus pubescens Willd.) and one evergreen (Quercus ilex L.) European oak. Mean cold hardiness values in January were –56, –45 and –27 °C for Q. robur, Q. pubescens and Q. ilex, respectively. Soluble carbohydrate concentrations were closely related to instantaneous cold hardiness, estimated by the electrolyte leakage method, whereas total carbohydrate concentration was related to maximum cold hardiness. Both cold hardiness and carbohydrate concentration showed a close linear relationship with temperatures at the location of the sampled population. Our results show that temporal variation in both the inter- and intraspecific cold hardiness in European oaks can be related to variations in the concentrations of soluble carbohydrates and that these relationships appear to be driven by temperature.
10.1093/treephys/27.6.81710.1093/treephys/27.6.817
Keywords: adult individuals; climate; distribution; frost dam- age; natural populations; Phenology; Quercus ilex; Quercus pubescens; Quercus robur

Identification, measurement and interpretation of tree rings in woody species from mediterranean climates. - Cherubini, Paolo; Gartner, Barbara L.; Tognetti, Roberto; Bräker, Otto U.; Schoch, Werner; INNES, JOHN L. (Biological reviews of the Cambridge Philosophical Society, 2003)
We review the literature dealing with mediterranean climate, vegetation, phenology and ecophysiology relevant to the understanding of tree-ring formation in mediterranean regions. Tree rings have been used extensively in temperate regions to reconstruct responses of forests to past environmental changes. In mediterranean regions, studies of tree rings are scarce, despite their potential for understanding and predicting the effects of global change on important ecological processes such as desertification. In mediterranean regions, due to the great spatio-temporal variability of mediterranean environmental conditions, tree rings are sometimes not formed. Often, clear seasonality is lacking, and vegetation activity is not always associated with regular dormancy periods. We present examples of tree-ring morphology of five species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Q. ilex, Q. pubescens) sampled in Tuscany, Italy, focusing on the difficulties we encountered during the dating. We present an interpretation of anomalies found in the wood structure and, more generally, of cambial activity in such environments. Furthermore, we propose a classification of tree-ring formation in mediterranean environments. Mediterranean tree rings can be dated and used for dendrochronological purposes, but great care should be taken in selecting sampling sites, species and sample trees.
The following values have no corresponding Zotero field: accession-num: 12620063
Keywords: Arbutus unedo; Dendrochronology; Dendroecology; ecophysiology; Fraxinus ornus; Mediterranean climate; mediterranean tree rings; Mediterranean vegetation; Phenology; Quercus cerris; Quercus ilex; Quercus pubescens; wood anatomy

Co-occurrence of trees with different leaf habit: A functional approach on Mediterranean oaks - Damesin, Claire; Rambal, Serge; Joffre, Richard (Acta Oecologica, 1998)
Tree species can be split into two groups in terms of their leaf life-spans: evergreens and deciduous. Their distinct geographical dis- tribution suggests that these two groups have functional characteristics adapted to specific environments. However, deciduous and evergreen trees co-exist in some regions, such as those with a Mediterranean climate. They provide good models for comparing the properties of both trees and obtaining an understanding of how diversity is maintained. This is the case in southern France, where the evergreen holm oak (Quercus ilex) and the deciduous downy oak (Quercus pubescens) co-exist. A research programme has been conducted which compares the functioning of these two species at various scales, with the aim of anticipating their distribution in the event of climatic change. The ‘cost-benefit‘ model of Mooney and Dunn has been tested at leaf scale. Q. pubescens has a lower area-based construction cost than Q. ibex, but does not have a higher photosynthetic capacity. Despite differences in biochemical composition, size and mass per unit area, the leaves of the two species respond similarly to limited water conditions. Furthermore, the carbon isotope composition suggests that they have similar intrinsic water-use efficiencies. At the ecosystem scale, preliminary data are available on water, carbon and nitrogen use: i) measurements of leaf water potentials show that drought constraint starts at the same time and with the same rate and intensity in both species: ii) leaf area index was higher in Q. ilex woodlands; and iii) the release rate of nitrogen from the litter was faster in Q. ilex ecosystems. Together, these results indicate that the key factors distinguishing functions of deciduous and evergreen Quercus are more apparent at the ecosystem level than at the leaf level
Keywords: carbon isotope composition; construction cost; deciduous tree; evergreen tree; leaf area index; leaf gas exchange; Leaf habit; Mediterranean-type climate; nitrogen content; Quercus ilex; Quercus pubescens

Retrieving leaf conductances from sap flows in a mixed Mediterranean woodland: a scaling exercise - Filho Teixeira, José; Damesin, Claire; Rambal, Serge; Joffre, Richard (Ann. For. Sci., 1998)
Xylem sap-flux densities were monitored continuously using Granier-type sensors on five Quercus ilex, four Arbutus unedo and one Quercus pubescens from June 1993 to October 1994. Half-hourly measurements of incoming solar radiation, air temperature and humidity, horizontal wind speed and precipitation were carried out at the top of a tower at a height of 12 m, about 2 m above the canopy. Leaf physiological measurements (stomatal conductance, water potential) on individual sunlit leaves from each of the three tree species were obtained on seven complete or partial diurnal time courses. For these three species, to estimate leaf stomatal conductance, we used the big-leaf approach of Penman-Monteith. We have divided the leaves into sunlit and shaded. The model sums the individual-leaf model for only the sunlit fraction to produce the whole-canopy predictions. Transpiration was deduced from sap flux through a transfer function taking into account stem water storage. Stomatal conductance for a given species was evaluated half-hourly from transpiration and microclimate data inverting the Penman-Monteith equation. An empirical model was identified that related stomatal aperture to simultaneous variations of microclimate and plant water potential for the 1993 period. The predicted leaf conductances were validated against porometer data and those of the 1994 period. The diurnal patterns of predicted and measured transpiration indicated that stomatal conductance was accurately predicted. The leaf conductance models were also compared with already published literature values from the same tree species. In spite of the simplifications inherent to the big-leaf representation of the canopy, the model is useful for predicting interactions between Mediterranean mixed woodland and environment and for interpreting H2 O exchange measurements
Keywords: Arbutus unedo; mixed Mediterranean woodland; Penman-Monteith equation; Quercus ilex; Quercus pubescens; sap flow; stomatal and canopy conductances

Germination and regeneration mechanisms in Mediterranean degenerate forests - Bacilieri, R.; Bouchet, M. A.; Bran, D.; Grandjanny, M.; Maistre, M.; Perret, P.; Romane, F. (Journal of Vegetation Science, 1993)
Abstract. Germination and developmental behaviour during juvenile stages are of importance in relation to succession mechanisms acting on plant communities. This is particularly so in the Mediterranean region, where the climatic summer drought causes stress. We investigated and compared germination and development of four tree species in two parts of the French Mediterranean region where the original dominant tree species (Quercus pubescens) has been largely replaced by Quercus ilex in the southern part, and Castanea sativa in the northern part. Observed differences in germination rates and developmental behaviour, especially shootroot ratio and the role of water supply, suggest that other species may eventually replace the current dominant species.
The following values have no corresponding Zotero field: publisher: Blackwell Publishing Ltd
Keywords: Castanea sativa; Pinus pinaster; Quercus ilex; Quercus pubescens

What are the consequences of being a downy oak (quercus pubescens) or a holm oak (Q. ilex) for breeding blue tits (Parus caeruleus)? - Blondel, J.; Isenmann, P.; Maistre, M.; Perret, P. (Plant Ecology, 1992)
By comparison with deciduous oaks, the lower yearly production of new leaves in sclerophyllous oaks is hypothesized to have several consequences on animal communities. In particular, the production of arthropod communities that feed upon the leaves should be lower in sclerophyllous than in deciduous oaks, this causing changes in breeding patterns and the demographic balance in insectivorous birds. Studies in both deciduous and sclerophyllous habitats in southern France have shown that: 1) the spring development of new leaves occurs later and more slowly in sclerophyllous than in deciduous oaks, 2) the biomass of caterpillars is much lower in sclerophyllous oak forests, and 3)there is a large variation in life history traits of the Blue Tit depending in which type of habitat they breed. Laying date occurs later and clutch size is lower in sclerophyllous habitats than in deciduous habitats. The evolution of life history traits is discussed according to whether poor sclerophyllous habitats are isolated (e.g. on Corsica) or are parts of landscapes including both habitat types.
Keywords: breeding traits; caterpillars; leafing phenology; Parus caeruleus; Quercus ilex; Quercus pubescens